The role of platelet indices in ischemic heart disease: a hospital based case control type of study - Gandhi, Priyanka S.; Gamit, Bhavna N. (International Journal of Research in Medical Sciences, 2019)
Background: In developing countries, Ischemic heart diseases (IHD) is one of the leading causes of morbidity and mortality. The underlying pathology of CAD is atherosclerosis. When this atherosclerotic plaque ruptures, platelets play a crucial role in the prothrombotic events and forms a thrombus on this plaque and as a result coronary artery gets occluded causing ischemia and infarction. Platelet contains many chemokines, cytokines and growth factors. Release of these factors along with interaction with endothelial cells and leukocytes promotes inflammation and progression of atherosclerosis. We aimed to investigate the association between platelet volume indices in patients with diagnosis of Ischemic heart disease in comparison with control group. Methods: By using automated cell counter platelet count and platelet volume indices - were compared with Normal healthy or non-cardiac chest pain patients with the use of unpaired t test. Results: In the present study, we demonstrated that platelet count is significantly low and MPV and PDW are significantly high in Ischemic heart disease as compared to patients with noncardiac chest pain or healthy subjects. The correlation of MPV with PC revealed an inverse correlation between the patients of IHD and healthy or non-cardiac chest pain patients which is statistically significant. Conclusions: The platelet volume indices are an important, simple, effortless and a cost-effective tool useful in predicting the development of an acute coronary event sometimes in the near future and therapeutic modification for improved patient’s cardiovascular care.